Subalternity in Joseph Conrad’s Heart of Darkness - Baskota, Dhananjaya (Damak Campus Journal, 2024)
Human civilization has a long history about power relation among the individuals and the societies. Power relations prominently try to 'other' them who are powerless, voiceless, socially backwards, culturally isolated and economically exploited. 'This paper presents how European elites make 'other' to the native Africans. The process of 'othering' establishes the idea of subalternity;which is reflected through the African natives in Joseph Conrad's novel Heart of Darkness.The native Africans are voiceless and put beyond the center of conversations among the non-African characters. The way of keeping Africans at bay is found in the novel; and they are made only slaves. This study tries to explore how subalternity is reflected in Joseph Conrad’s Heart of Darkness. Furthermore, this novel is viewed in this article from the subaltern perspectives proposed by Antonio Gramsci (1891-1937) Gayatri Chakravorty Spivak (1942), Ranajit Guha (1923-2023) using the qualitative research. The novel has reflected subalternity after the input of sources; and this is discussed for the objective conclusion.